2000
DOI: 10.1096/fj.99-1049com
|View full text |Cite
|
Sign up to set email alerts
|

VEGF‐C and VEGF‐D expression in neuroendocrine cells and their receptor, VEGFR‐3, in fenestrated blood vessels in human tissues

Abstract: Recently, vascular endothelial growth factor receptor 3 (VEGFR-3) has been shown to provide a specific marker for lymphatic endothelia in certain human tissues. In this study, we have investigated the expression of VEGFR-3 and its ligands VEGF-C and VEGF-D in fetal and adult tissues. VEGFR-3 was consistently detected in the endothelium of lymphatic vessels such as the thoracic duct, but fenestrated capillaries of several organs including the bone marrow, splenic and hepatic sinusoids, kidney glomeruli and endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
230
2
4

Year Published

2000
2000
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 301 publications
(248 citation statements)
references
References 43 publications
12
230
2
4
Order By: Relevance
“…34 More recent data show the VEGFR-3 can also be expressed on blood vessel endothelium, for example, in fenestrated capillaries. 35 We and others also found that VEGFR-3 is expressed and upregulated on blood vessels during fetal development, in tumors and in chronic wounds, together with the corresponding ligand VEGF-C. 36,37 VEGFR-3 can also be weakly expressed in the capillary endothelium of normal breast tissue as well. Thus, when measuring VEGFR-3 levels in tissues, possible contributions from cell types in addition to lymphatic endothelial cells should be taken into consideration.…”
Section: Discussionmentioning
confidence: 86%
“…34 More recent data show the VEGFR-3 can also be expressed on blood vessel endothelium, for example, in fenestrated capillaries. 35 We and others also found that VEGFR-3 is expressed and upregulated on blood vessels during fetal development, in tumors and in chronic wounds, together with the corresponding ligand VEGF-C. 36,37 VEGFR-3 can also be weakly expressed in the capillary endothelium of normal breast tissue as well. Thus, when measuring VEGFR-3 levels in tissues, possible contributions from cell types in addition to lymphatic endothelial cells should be taken into consideration.…”
Section: Discussionmentioning
confidence: 86%
“…We have shown that mRNA for VEGF-A, -B, -C and -D is present within B16 and B16/IL-12 tumours grown in vivo (data not shown). Initially, it was thought that VEGFR-2 was expressed on both blood vascular and lymphatic endothelial cells, whereas VEGFR-3 expression was limited to lymphatic vessels and fenestrated endothelium (Partanen et al, 2000). However, more recently it has been clearly demonstrated that VEGFR-3 expression is upregulated on the blood vessels within tumours of multiple types including melanoma, colon and breast (Valtola et al, 1999;Achen et al, 2001;White et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Later in development, the VEGFR-3 expression becomes restricted mainly to lymphatic vessels (Kaipainen et al, 1995;Kukk et al, 1996). Recently, it has also been shown, that in addition to lymphatic endothelium, VEGFR-3 is expressed in tumor blood vessels during neovascularization (Valtola et al, 1999) and in some fenestrated endothelia (Partanen et al, 2000). The VEGFR-3 ligand VEGF-C is mitogenic towards lymphatic endothelial cells and it showed a selective lymphangiogenic response in di erentiated avian chorioallantoic membrane (Oh et al, 1997).…”
Section: Lymphangiogenic Role Of Vegfr-3mentioning
confidence: 99%